The British organ and its music during the nineteenth century - Wise, James Patrick Gerald (Rhodes University, Faculty of Humanities, Department of Music, 1957)
It is a curious fact that, although the literature of the organ is a reasonably large one, no attempt has been made to study the history of the instrument in Britain in any detail. Hopkins and Rimbault covered a certain amount of ground up to 1800, but even they could not deal very extensively with the subject in a volume that was tracing the history of the organ not only in Britain, but throughout Europe, and not only its history but its construction also. For similar reasons Dr. Sumner? (name unclear), in his recent book, could paint little more than an outline picture. However, the British organ's development prior to 1800 was one that does not admit of very discursive treatment. Progress was lamentably slow in comparison with that of Continental organs; and consequently the nineteenth century dawned with British organ-building literally hundreds of years behind that of France, Germany, Belgium and Holland. Yet, a century later, the position was redeemed, and even before the present era opened, the products of British organ-builders were not merely equal to, but, in general superior to those of the Continent in tonal design, mechanism, in artistic finish, and in ordinary maintenance and preservation. The nineteenth century, then, must clearly be regarded as a remarkable, indeed glorious, period in British organ-building, in fact one is tempted to enquire, whether there exists, in the entire artistic and scientific history of any country a similar example of accelerated development; in which one country has made up three hundred years' leeway in one third of that time. This thesis therefore, sets out to examine and describe the events of the century, and the men who were responsible for those events, to trace the growth of the organ in its various departments, and as the instrument itself is only a means to an end, to say something about the way in which it was used, the music that was played on it, and the men who played and composed this music. The thesis is divided into two volumes, the first deals entirely with the history of the instrument and its builders during the nineteenth century, with an introduction briefly recounting the story from the Restoration up to the year 1800; and the second volume is concerned with the music and the musicians as well as the several detailed indexes which are so necessary if a work of this kind is to be of any value at all. A full bibliography is given in Volume Two, but supreme acknowledgement must be paid here to the quarterly periodical "The Organ" - still thriving after an active career that began in July 1921. Its scholarly articles range over the whole field of international organ-building and organ-history, and without its help this thesis would have been far less comprehensive in its scope and far lesss authorative in its source-material.
Keywords: Uncatalogued